Comparison Analysis of Portfolio Using Markowitz Model and Single Index Model: Case in Jakarta Islamic Index - Tri Yuwono; Dadan Ramdhani (Penerbit Kemala Indonesia, 2017)
The aim of this research are to establish the optimal portfolio of stocks listed on the Jakarta Islamic Index in Indonesia Stock Exchange in order to observe and measure their performance potential as a financial investment instrument for the people to invest in the capital market in Indonesia. Furthermore, this study offers a better choice in the decision making process in selecting the optimal portfolio of stocks listed on the Jakarta Islamic Index in Indonesia Stock Exchange using the modern theory of portfolio formation markowitz model and single index model. The sample used in this study is a company that always appear in the announcement of changes to the composition of stocks in the Jakarta Islamic Index in Indonesia Stock Exchange during the period 2010-2016. The sampling method used in this research using purposive sampling method. The analysis method used in this study using wilcoxon test with statistical software. The results showed that there was no significant difference between the level of return earned by using markowitz model and single index model, and the level of return earned by using markowitz model and single index model is not higher than the risk-free asset return.